Factors Associated With Low Tuberculosis Case Detection and Investigation in Public Health Facilities (PHFs) in Bududa District, Uganda: A Cross‐Sectional Study - Imelda Tumuhairwe; Alimah Komuhangi; Alfred Okello; Apolo Ayebale; Ambrose Wabwire Buyinza; Godfrey Bwire (Health Science Reports, 2025)
ABSTRACT Background and Aims Despite global efforts to combat tuberculosis (TB), Uganda bears a high burden, with an annual incidence of 200 per 100,000 and a mortality rate of 35 per 100,000 persons. This study investigates TB prevalence, detection rates, and associated factors in public health facilities (PHFs) in Bududa district. Methods A cross‐sectional study employing Mixed Methods Research (MMR) was conducted in November 2019 on respondents with symptoms suggestive of TB and key informants overseeing TB care in Bududa district, Uganda. Results Only 18.8% (46/245) of respondents who reported symptoms suggestive of TB were investigated for infection. The majority, 87.4%, never had sputum requested and 91.7% never had a chest X‐ray done. Participants from rural areas were 26% less likely to be screened for TB than their urban counterparts (PR = 1.26, 95% CI [1.16–1.38]). Challenges for TB care included staffing shortages and inadequate medical supplies and equipment. Conclusion This study highlights the disparity between high TB burden and low detection rates in Bududa district. The Government of Uganda and stakeholders should invest in solving the challenges identified by this study.